Counseling on How to Make and Apply Organic Fertilizers in Jabung Village, Ponorogo Regency - Triani, Nova; Syafriani, Elly; Somala, Medina Uli Alba (Nusantara Science and Technology Proceedings, 2020)
The use of organic fertilizers can improve soil conditions. Soil conditions include soil structure and health. The soil structure that has good aeration and drainage can increase plant productivity. The content of organic matter and microorganisms in healthy soil can be beneficial for sustainable agriculture. Making organic fertilizers can take advantage of the remains of organic matter or dry leaf litter around the environment. Appropriate application of organic fertilizers can affect plant growth and development as well as the quality of crop yields. Plant growth and development can affect plant productivity. High plant productivity and good quality yields can increase the selling value of the crop. The selling value of high yields can increase income and increase the welfare of farmers. Food crops such as vegetables can use organic fertilizers so that vegetables become healthier. Farmers can also reduce spending on inorganic fertilizers or chemical fertilizers. Making organic fertilizers can also be a business opportunity for farmers. The purpose of this community service activity is to provide counseling on how to making and apply organic fertilizers, especially for vegetable crops. The counseling participants came from the Ponorogo Organic Farming Community in Jabung Village, Ponorogo Regency. Outreach to farmers using lectures, presentations, video screenings, and interactive discussions. Farmers' understanding increased by 37.5% on how to make and apply organic fertilizers. On average, farmers have an initial understanding level of 30%. After receiving counseling, the farmers' understanding increased to 67.5%.